The Way to Get Rid of the Acquired Unlawful Property (Salam International Academic Journal, 2022)
This article deals with the issue of getting rid of unlawfully acquired property. First, it talks about earning property lawfully and how the Islamic Sharia paid great deal of attention to the issue of property, and considered its preservation one of its five objectives. In addition, Islamic Sharia insisted on earning money in legitimate ways as proven by the clear texts of The Holy Qur’an, the Sunnah and the efforts made by the Muslim jurists in the light of Qur’an and Sunnah. Next, the article discusses the types of property that people obtained illegally and mentioned the concept of unlawful wealth that it is all the money which the Sharia prohibited a Muslim from acquiring and owning due to the presence of an impediment that prevents it, which Allah called it void. The forbidden property is a property which is either taken unfairly, namely through theft, treason or usurpation, or obtained via any prohibited way or unlawful act, such as gambling, the wages of prohibited acts, the price of wine, pork, the dowry of a prostitute, and the wages of a priest. Then this study elaborated the ways to get rid of unlawful money, and that it is not permissible for a Muslim to acquire such money and save it, but rather he must get rid of it through the ways shown by Sharia scholars, which are returning this money to its owners or spending it in good ways with the intention of getting rid of it, not for getting closer to Allah, and it is not permissible for him to benefit from it or spend it for his own interests.